The sustainable development in Portuguese higher education institutions: An exploratory study of students' perceptions - Aleixo, Ana Marta (2020)
Purpose: This study presents a descriptive and exploratory research about the understanding of sustainable development (SD) among public higher education institutions’ students, in Portugal. It explores the student’s perspectives about SD through the analysis of their attitudes, skills and experiences on the theme. Their knowledge about sustainable development goals (SDGs), and their opinion about the importance of SD as future professionals were also under consideration. Method: The research design of the study follows a descriptive and exploratory approach with a quantitative reporting of results. It was used an on-line questionnaire, adapted from the National Union Students (2018), to obtain the data. A sample of 1257 students from the Portuguese public higher education institutions (HEIs) was obtained. Findings: Students consider that HEIs can do more in terms of education for SD namely: (i) offer free SD courses/workshops; (ii) streamline/develop actions on SD; (iii) encourage volunteer actions in the community, and (iv) promote student participation in practical on-campus actions. Students also consider that secondary education was the educational path that most encouraged to think and act in ways that help the environment and people. Most students already have heard about SDGs and know what they are, however, only a small number of students are actively involved in activities organized by their HEI. Research limitations: This research has a national scope. Social implications: This study provides valuable insights for future implementation processes supporting the integration to sustainability in HEIs. Originality/value: The study helps to better understand the students’ perceptions about SD and the role of HEIs to improve it, namely in Portugal where the studies about the theme are scarce. The results could be used by HEIs to introduce the SD topics in formal and informal education, as well as to improve it integration on campus activities.